Learning Management of TPQ Al-Hilal Malang in Solving Illiteracy Reading The Quran and Increasing Student Creativity - Wahyudi Widodo (Jurnal Indonesia Sosial Teknologi, 2024)
Al Quran Education Park is a non-formal educational facility that aims to improve the ability to read and write the Quran and understand Islam. The number of bad records regarding the management of the Qur'an Education Park (TPQ) and the large number of generations of Indonesian Muslims who are illiterate of the Qur'an seems to be caused by a lack of knowledge of the Qur'an and implementing learning management properly and correctly. This study aims to describe learning management in the Al-Qur'an Al-Hilal Education Park Malang. This research uses qualitative or field. The results obtained in the learning planning stage are held monthly between the management and the ustadz/ustadzah. In organizing learning, learning grouping activities consist of TPQ al-Hilal consisting of group division, division of guardians and group assistants, compiling, student entrance schedules, learning implementation times, determining the material to be taught, and choosing the method used. In the implementation of learning, it consists of 3 stages of learning, namely introduction, core, and closing. In the evaluation of learning at TPQ al-Hilal, there are two evaluations: monthly and annual. The learning used the UMMI Qur'an method and added creative archery, coloring, or calligraphy activities.